Effects of cannabis regulation in Switzerland: Study protocol of a randomized controlled trial - Baltes-Flueckiger, Lavinia; Steinauer, Regine; Meyer, Maximilian; Vogel, Marc; Walter, Marc (Frontiers in Psychiatry, 2023)
Background Cannabis is the most widely used illicit substance. Various countries have legalized cannabis for recreational use. Evidence on the health effects of cannabis regulation remains unclear and is mainly based on observational studies. To date, there is no randomized controlled study evaluating the impact of cannabis regulation for recreational use compared to the illicit market on relevant health indicators. The present study (“Weed Care”) is the first to evaluate the impact of regulated cannabis access in pharmacies versus a waiting list control group representing the illicit market on problematic cannabis use as well as on mental and physical health. Methods The study is divided into two parts—a randomized controlled study of 6 months followed by an observational study of 2 years. Participants (N = 374) are randomly assigned to either the experimental group with access to legal cannabis in pharmacies or to the waiting list control group representing the current legal framework in Switzerland, namely the illicit market. After 6 months, all participants will have access to legal cannabis for the following 2 years (observational study). The primary outcome is problematic cannabis use as measured with the Cannabis Use Disorders Identification Test-Revised (CUDIT-R). Secondary outcomes are cannabis use patterns, mental disorders (e.g., depression, anxiety, and psychosis) and physical health (e.g., respiratory symptoms). Primary and secondary outcomes will be assessed online every 6 months. The study is approved by the responsible ethics committee as well as by the Swiss Federal Office of Public Health. Discussion Findings from this study may provide a scientific basis for future discussions about addiction medicine and cannabis policy in Switzerland. Clinical Trial Registration ClinicalTrials.gov (NCT05522205). https://clinicaltrials.gov/ct2/show/NCT05522205